Globalization on trial : the human condition and the information civilization Farhang Rajaee.. - Raj?ay?i, Farhang, 1952 or 1953- (International Development Research Centre: Kumarian Press, 2000)
"What is the human condition at the dawning of the global age? Drawing upon his own extensive experience, as well as upon the thoughts of Western and "non-Western" scholars and philosophers, Farhang Rajaee provides a fresh and critical inquiry into the nature of globalization." "Globalization on Trial challenges the conventional view that equates globalization with the expansion of the capitalist economic system. With a broad historical and holistic brush, the author presents a view of globalization that is both multidisciplinary and multicultural. What opportunities must we seize? What dangers must we overcome? Rajaee examines human governance and the paradox of globalism and nationalism (or "nativism"), providing a particularly fresh perspective on Islamic civilization. He also focuses on our education system and how it will have to adapt to meet the new challenges of our global, information age." "Globalization on Trial will interest researchers, scholars, and students in the social sciences and, particularly, the humanities; donors, development organizations, NGOs, and development practitioners; and anyone concerned with how globalization and the information revolution are affecting the nature of human civilization, and with the interaction between Islamic and Judeo-Christian (or "Western") civilization. Book jacket."--Jacket.